The incidence of postoperative cognitive dysfunction in elderly patients underwent elective surgery at Sanglah General Hospital - Pontisomaya Parami; Christopher Ryalino (Bali Journal of Anesthesiology, 2020)
Background: Postoperative cognitive dysfunction (POCD) causes an increase in social and economic burdens because of the prolonged length of stay in the hospital, increased costs, and decreased quality of life. No data on POCD has ever been recorded in Indonesia. The goal of this study was to determine the incidence of POCD in elderly people at Sanglah General Hospital, Indonesia. Patients and Methods: This is a descriptive study conducted at Sanglah General Hospital in 2018. Inclusion criteria included patients of 60 years old or more who came to anesthesia preoperative clinic with the American Society of Anesthesiologists physical status 1 and 2. Cognitive functions were assessed three times: 1 day before the surgery, 2 days after the surgery, and 4 weeks after the surgery. POCD was defined as an at least 20% decreased result of two out of three instruments used. Results: The study included 84 participants consisting of 52 males and 32 females. The mean age was 66.0 ± 5.1 years. Most participants were elementary school graduates (34.5%) and high school graduates (27.4%). There were 7 (8.3%) patients who developed POCD within 48 h and 4 weeks postoperatively. Conclusion: The incidence of POCD at Sanglah General Hospital was 8.33% both at 48 h and 4 weeks postoperatively.